Tobacco Smoking, Lung Cancer, and Therapy in Iraq: Current Perspective - Ibrahim, Buthainah A.; Al-Humaish, Saif; Al-Obaide, Mohammed A. I. (Frontiers in Public Health, 2018)
Abstract Tobacco smoking is a research topic of high interest to the public health in Iraq. Although Iraq is a country with a high percentage of smokers, we noticed the dearth of adequate studies and programs to deal with this problem. The percentage of smokers exceed 30 percent of the population and smoking problem becomes a permanent habit in adults and young people. The problems associated with tobacco smoking behavior related to individuals' post-traumatic stress disorder following post-war conflicts, and the social and cultural environment. The health consequences of tobacco smoking can harm almost every organ in the body, and there are reports confirmed the tobacco smoking is a high-risk factor for lung cancer and other diseases. The relative risk of lung cancer increases with increasing duration and intensity of smoking. Also, smoking associated with bladder, prostate, and head and neck cancers, in addition to respiratory diseases. Intervention efforts should focus on reducing the prevalence of cigarette smoking, introduce effective treatments for cancer and quit smoking. In this perspective article, we present our viewpoint and three scenarios to deal with the problem of tobacco smoking in Iraq. We recommend introducing educational, health and legislative policies for quitting smoking and using effective treatments for cancer.